Current Study of RhoA and Associated Signaling Pathways in Gastric Cancer - Liu, Haiping; Liu, Yiqian; Zhang, Xiaochuan; Wang, Xiaodong (Current Stem Cell Research & Therapy, 2020)
Gastric cancer (GC) is the fourth-most common cancer in the world, with an estimated 1.034 million new cases in 2015, and the third-highest cause of cancer deaths, estimated at 785,558, in 2014. Early diagnosis and treatment greatly affect the survival rate in patients with GC: the 5-year survival rate of early GC reaches 90%-95%, while the mortality rate significantly increases if GC develops to the late stage. Recently, studies for the role of RhoA in the diseases have become a hot topic, especially in the development of tumors. A study found that RhoA can regulate actin polymerization, cell adhesion, motor-myosin, cell transformation, and the ability to participate in the activities of cell movement, proliferation, migration, which are closely related to the invasion and metastasis of tumor cells. However, the specific role of RhoA in tumor cells remains to be studied. Therefore, our current study aimed to briefly review the role of RhoA in GC, especially for its associated signaling pathways involved in the GC progression.
Keywords: NF-kappaB